IMPLEMENTATION OF EXPIRATION LABELIZATION OF HOUSEHOLD INDUSTRIAL FOOD PRODUCTS (P-IRT) - Muhammad Nuqlir Bariklana; Tika Ifrida Takayasa; Siti Azizah (GEMA PUBLICA, 2023)
Food product labeling is one of the policies to ensure the quality of food products consumed by the public. The labeling policy is regulated in PP no.69 of 1999. One of the labeling policies is the obligation of food producers to include the product expiration date. Almost every year, a lot of findings of food products, especially the results of household industrial food products (P-IRT). This study seeks to formulate why the implementation of the PIRT expiration labeling policy is still not optimal. From the results of the study it was found that several factors influenced the implementation of this policy. The first was PIRT certification, especially at the extension stage and producer location review. The second is the understanding of PIRT producers regarding the expiration labeling. The third is limited human and financial resources. Fourth, consumers' concern that is still lacking is mainly related to attention to the expired labels of food products they consume.Keyword: Implementation, Labeling, Food, Expiration, Consumers